2019
DOI: 10.1111/ijfs.14087
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of the in vitro activities of α‐amylase, α‐glucosidase and pancreatic lipase by yellow field pea (Pisum sativum L.) protein hydrolysates

Abstract: Summary The aim of this work was to produce yellow field pea protein‐derived peptides as inhibitors of α‐amylase, α‐glucosidase and pancreatic lipase activities. A pea protein concentrate was hydrolysed with alcalase, chymotrypsin, pepsin or trypsin and the hydrolysates separated into different fractions (<1, 1–3, 3–5, 5–10 kDa) by membrane ultrafiltration. Peptide sequence analysis showed that the alcalase hydrolysate had higher levels of di‐ and tripeptides when compared with the chymotrypsin, pepsin and try… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
89
2
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 111 publications
(107 citation statements)
references
References 50 publications
12
89
2
4
Order By: Relevance
“…α‐amylase and α‐glucosidase are key enzymes involved in the digestion of dietary starch, releasing oligosaccharides that can be further broken down to glucose, which is rapidly absorbed by the body. Therefore, the inhibition of α‐amylase/α‐glucosidase activities is regarded as an effective strategy for managing diabetes and weight gain (Awosika & Aluko, ).…”
Section: Resultsmentioning
confidence: 97%
“…α‐amylase and α‐glucosidase are key enzymes involved in the digestion of dietary starch, releasing oligosaccharides that can be further broken down to glucose, which is rapidly absorbed by the body. Therefore, the inhibition of α‐amylase/α‐glucosidase activities is regarded as an effective strategy for managing diabetes and weight gain (Awosika & Aluko, ).…”
Section: Resultsmentioning
confidence: 97%
“…α-glucosidase is another enzyme that makes glucose available in the body by breaking down oligo- and disaccharides, converting them into absorbable monosaccharides. Therefore, in order to reduce serum glucose levels and manage related diseases, α-glucosidase inhibition has been proposed as a suitable approach [ 33 , 34 ]. This work showed that the vegetable extracts had weaker α-glucosidase inhibition than acarbose, the drug.…”
Section: Discussionmentioning
confidence: 99%
“…Sequences of collagens (11), mainly collagen type I chains, were derived from the UniProt database of protein sequences (shortly, UniProt database) (providers: Swiss Institute of Bioinformatics, Lausanne, Switzerland and European Bioinformatics Institute, Hinxton, UK) [21] (http:/www.uniprot.org). They represented collagens derived from cow (Bos taurus; P02453), pig (Sus scrofa; A0A287BLD2), sheep (Ovis aries; W5P481), chicken (Gallus gallus; P02457), duck (Anas platyrhynchos platyrhynchos; A0A493T0N1), horse (Equus caballus; F6SSG3), salmon (Salmo salar; A0A1S3S6G4), rainbow trout (Oncorhynchus mykiss; O93484), goat (Capra hircus; A0A452FHU9), rabbit (Oryctolagus cuniculus; A0A5F9CPN0), and turkey (Meleagris gallopavo; G1NB83).…”
Section: Methodsmentioning
confidence: 99%
“…The biological function of individual peptides is also related to the inhibition of: angiotensin I-converting enzyme (ACE; EC 3.4.15.1), dipeptidyl peptidase IV (DPP-IV; EC 3.4.14.5), α-glucosidase (EC 3.2.1.20), α-amylase (EC 3.2.1.1) [10], and lipase (EC 3.1.1.3) [11]. The ACE-inhibiting activity of peptides contributes to the blood pressure reduction in humans and animals [12], while inhibitors of lipase are involved in combating obesity [11]. In contrast, other aforementioned enzyme inhibitors are involved in the regulation of blood sugar level (antidiabetic peptides) [10].…”
Section: Introductionmentioning
confidence: 99%